Ordered nuclear systems - Hobden, M (1960)
In this thesis are described further developments in the design and construction of apparatus for producing very low temperatures by the technique of adiabatic demagnetization of nuclear spin systems, a technique proposed independently in 1934 by Gorter and by Kurti and Simon. Improved methods of measuring nuclear susceptibilities have led to a more accurate estimate of the value of θn, the nuclear interaction temperature, for copper nuclei in copper metal. It is shown that θn is four times smaller than the value estimated by Spohr in his earlier experiments and is in fact close to the theoretical value for magnetic dipole interaction. The nuclear spin-conduction electron relaxation time has been measured at various temperatures and this is discussed in relation to nuclear spin relaxation theories. The cryostat designed for these experiments is described in some detail. A metal helium dewar of large capacity has been designed with close spaced walls in the tail to make best use of the small internal diameter of the high powered solenoid for producing the strong magnetic fields. The advantages of this particular vessel are explained. A closed circuit He3 system is described which enables a thermal shield to be maintained at 0.35°K. This overcomes the disadvantages of the thermal shield cooled by a separate paramagnetic salt, as used by Spohr, allowing the temperature of the paramagnetic heat sink to be measured. This He3 system was designed to work on the principle of initial condensation at 1°K followed by pumping with a diffusion pump to 0.35°K, using 0.2 cm3 of liquid (150 cm3 of gas at N.T.P.). Subsidiary experiments are described to test the performance of this system. An A.C. method of measuring the nuclear susceptibility has been developed to replace the previous ballistic system. This method employed a balanced A.C. bridge which was unbalanced by the nuclear susceptibility. It was so arranged that the proximity of large masses of metal did not affect the measurements. The improvement in technique has shown that the form of decay of the nuclear susceptibility is exponential and not linear as previously assumed allowing more accurate values of the nuclear spin temperature at the instant of demagnetization to be found. The lowest spin temperature achieved was 1.3 × 10-6 °K. It is shown also that the conduction electrons do not become cooled to these temperatures as previously thought. Experiments on copper give a nuclear interaction temperature θn = 1.75 × 10-7 °K where θn is defined in terms of the splitting of the nuclear energy levels due to the internal field. The value of θn is calculated using the expression θn = (μn Tf Hi)⁄(k I Ti) where Ti and Hi are the initial temperature and field before demagnetization, Tf is the final spin temperature and μn and I are the nuclear magnetic moment and spin. This value is equal, within the range of experimental and theoretical uncertainty, to that computed on the basis of magnetic dipole, indirect exchange, and pseudo-dipolar interactions. This would seem to Indicate that quadrupole splitting is not as important as previously assumed. The relationship of this θn to the Curie temperatures of the theories of nuclear ferromagnetism is discussed. The nuclear spin relaxation time τ has been measured with conduction electron temperatures in the range .012°K to 0.10°K. Those experiments showed the inverse relation of τ and Te, the conduction electron temperature. Furthermore the values of τ Te (which in this case were measured in zero field) were found to be a factor 3.5 times smaller than those found by Redfield in an extorted field, using nuclear resonance techniques, above 1°K. Application of an external magnetic field caused the relaxation time to increase. These results are discussed with reference to the theories of nuclear relaxation in metals by Korringa and more recently by Redfield.